PENGARUH JOB INSECURITY, STRES KERJA, DAN BEBAN KERJA TERHADAP TURNOVER INTENTION DI PT. AGRO PRIMA SEJAHTERA LAMPUNG - Nurma Yunita; Renanda Prastika; Vicky F Sanjaya; NurAzizaturrahma Azizah (Universitas Ngudi Waluyo, 2020)
ABSTRACT The purpose of this research is to find out the effect of job insecurity, workstress and workload on turnover intention on PT employees. Agro PrimaSejahtera Lampung. This research uses quantitative research methods anddata collection techniques by observation and questionnaire. The analysismethod uses the help of SmartPLS 3.0 testing software by testing thevalidity and reliabelity and significance test using t-statistics. The results ofthis study showed that job insecurity variables have a significant effect onturnover intention, work stress has a significant positive effect on turnoverintention and workload variables have a significant positive effect onturnover intention